Acerca de nuevas y viejas inscripciones (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper for kamasiosuei ikenionke setantunos possible segmentations are analysed; so a PN kamasio (gen.sg.) is isolated from the reflexiv form suei; ikenionke could be an abl. sg. with lack of the ending -z, if we GRQ'W PXVW UHDG ikenion[tes] ke[nteis]. For the PN setantunos *seȤtam ³VH- YHQ´ LV SURposed as derivation basis, in a word-formation *seȤtan-to- with other  parallels  in  the  Celtiberian  onomastics  (suostun-,  nouanto-).  For K.0.13 the lection tuinikukuei kortonikum kar is proposed, where the best of the choices seems to be the identification of kuei as sg. nom. of a indefinite enclitic pronoun, cognate of the sg. nom. interrogative *NX֒ eL֒  > oi. cía. In ]rkue | T utai | batikan | toulo | izui a 3th pl. tikan(to) is identificated, in connection with the verbal forms -tinkounei, -tiseti of BB.I. The subject of tikan(to) would be utaiba, if pl. ntr.; T is a numerical sign, and if it is not a cardinal,  perhaps  Tuta  VKRXOG  EH  UHDG  XWƗ  RU  ǌWƗ,  ³TXDUWHW, RFWHW´.